Physiological Response of Corynebacterium glutamicum to Increasingly Nutrient-Rich Growth Conditions - Graf, Michaela; Zieringer, Julia; Haas, Thorsten; Nieß, Alexander; Blombach, Bastian; Takors, Ralf (Frontiers in Microbiology, 2018)
To ensure economic competitiveness, bioprocesses should achieve maximum productivities enabled by high growth rates (µ) and equally high substrate consumption rates (qS) as a prerequisite of sufficient carbon-to-product conversion. Both traits were investigated and improved via bioprocess engineering approaches studying the industrial work horse Corynebacterium glutamicum. Standard minimal medium CGXII with glucose as sole carbon source was supplemented with complex brain-heart-infusion (BHI) or amino acid (AA) cocktails. Maximum µ of 0.67 h-1 was exclusively observed in 37 g BHI L-1 whereas only minor growth stimulation was found after AA supplementation (µ = 0.468 h-1). Increasing glucose consumption rates (qGlc) were solely observed in certain dosages of BHI ((1-10) g L-1), whilst 37 g BHI L-1 and AA addition revealed qGlc below the reference experiments. Moreover, BHI supplementation revealed Monod-type saturation kinetics of µ (KBHI = 2.73 g BHI L-1) referring to the preference of non-AAs as key boosting nutrients. ATP-demands under reference, 1 g BHI L-1 and AA conditions were nearly constant but halved in BHI concentrations above 5 g L-1 reflecting the energetic advantage of consuming complex nutrient components in addition to ‘simple’ building blocks such as AAs. Furthermore, C. glutamicum revealed maximum biomass per carbon yields of about 18 gCDW C-mol-1 irrespective of the medium. In AA supplementation experiments, simultaneous uptake of 17 AAs was observed, maximum individual consumption rates determined, and L-asparagine and L-glutamine were distinguished as compounds with the highest consumption rates. Employment of the expanded stoichiometric model iMG481 successfully reproduced experimental results and revealed the importance of C. glutamicum’s transaminase network to compensate needs of limiting AA supply. Model based sensitivity studies attributed the highest impact on µ to AAs with high ATP and NADPH demands such as L-tryptophan or L-phenylalanine.